The relationship between leadership behaviour and employees' retention in a finance institution / Norafidah Mohd Noor - Mohd Noor, Norafidah (2015)
Employee retention becomes one of the major issues in any organization. This might affect its turnover and further contribute to the productivity and long-term plan of an organization. Numerous studies have shown that leadership behaviour influences employee retention. Thus, this study is aimed to evaluate the retention rate and leadership behaviour exhibited among the superiors perceived by followers. The study was intended to examine the relationship between leadership behaviour and employees' retention in a private finance institution. A sample of 103 employees from Islamic Bank Malaysia Berhad in Selangor participated in this research. A 5-point Likert scale questionnaire consisting of 54 items was designed which were divided into 3 parts. Descriptive and inferential statistics were used to analyze the data. Apart from that, mean and standard deviation were also applied to analyze the retention rate among employees and the nature of leadership style of their superior. Correlation was used to analyze the relationship between leadership behaviour and employee retention. The reliability of the questionnaire as a whole is reported as high. The findings revealed that the employees perceived their company as high retention. The results also showed that the employees perceived that their superior exhibited a moderate transformational and transactional leadership behavior. However, the result depicted there was no significant relationship between leadership style and employees' retention rate. Implications for practice suggest that leaders are recommended to recognize their employees' work thus create an ideal work climate to ensure employees feel more comfortable in order for them to be a part of the organization.